Early childhood wheezing: various natural courses and their relationship to later asthma - Suh, Dong In (The Korean Pediatric Society, 2012)
Wheezing is one of the most frequent complaints that lead to the use of medical resources in younger children. Generally, wheezing is caused by bronchiolitis and resolves spontaneously without recurrence, but sometimes, wheezing can progress into asthma. Early data on the natural history of childhood wheezing was mostly obtained from retrospective reviews of medical records or from questionnaires, which made it difficult to exclude biases. Now that many cohort studies are available, reviewing the results of birth cohort studies makes it possible to understand the natural course of early childhood wheezing and the risk factors for asthma. In this study, we have reviewed the various phenotypes of early childhood wheezing and their natural courses to help select the most appropriate management modalities for the different types of early childhood wheezing.